Investigating Local Definitions of Sustainability in the Arctic: Insights from Post-Soviet Sakha Villages - Crate, Susan A. (ARCTIC, 2009)
Contemporary survival for post-Soviet Russia’s indigenous communities is complicated both by a Soviet legacy that undermined local ecological knowledge, kinship settlement patterns, land and resource rights, and robust ecosystems, and by the contemporary effects of globalization and modernity. Efforts to achieve sustainability lack a focus on local contexts, although recent research, especially in anthropology, underscores the need to develop sustainability criteria that are both flexible and adaptable to local contexts. Community-based research in post-Soviet Viliui Sakha indigenous communities of northeastern Siberia, Russia, has shown that inhabitants define sustainability as the building of local diversified economies, communities, and health via strong local leadership, a shared vision to work toward common goals, the reinstatement of local knowledge, and rights to land and resources. Realization of these ideas may be achieved by continued collaboration between circumpolar researchers and communities to facilitate the influx of ideas and models of success from other Arctic regions and by potential outcomes of intergovernmental action between the Russian Federation and its circumpolar neighbors through Russia’s chairing of the Arctic Council. Implementation of flexible, locally adaptable sustainability criteria is central to these efforts. La survie contemporaine des collectivités indigènes russes post-soviétiques est rendue complexe par un patrimoine soviétique qui minait le savoir écologique local, les tendances en matière de parenté, les droits à la terre et aux ressources, et les écosystèmes robustes, de même que par les effets contemporains de la mondialisation et la modernisation. Les efforts en matière d’atteinte de la durabilité ne portent pas suffisamment sur les contextes locaux, bien que des recherches récentes, notamment en anthropologie, fassent ressortir la nécessité d’élaborer des critères de durabilité qui sont à la fois souples et adaptables aux contextes locaux. Des recherches ...